Design and evaluation of the bearing capacity of high modulus asphalt concrete by means of a performance-based approach - Capitão, Silvino Dias (2003)
Pavement damage, induced by repeated passing of traffic coupled with climatic conditions, has a significant influence on the durability of roads. To improve the service life of pavements, innovative materials have to be used, with the aim of producing bituminous layers which could better resist distress phenomena, namely resistance to fatigue and to permanent deformation. Therefore, a project concerning the rehabilitation of a structural layer by using a high modulus bituminous mixture has been carried out. During the first stage, this study involved the laboratory design of the mix by conducting performance tests and constructing trial sections on the EN14 (Portuguese national road 14). In the next stage, specimens extracted from trial sections were submitted to a fundamental test (four-point bending) and a traffic simulation test (wheel tracking) to select the work mix formula to make the road base layer on the EN14. Finally, by using a compaction method which reproduces volumetric conditions obtained in the field, prismatic and cylindrical specimens have been produced in the laboratory. For several temperatures and loading conditions, fundamental tests have been performed (repetitive four-point bending and dynamic creep tests).